Competitive Transport Studies of Seven Metal Cations Through Bulk Liquid Membrane Using 1,4-Dioxa- 7,10-dithiacyclododecane-2,3-dione - HOSSEIN ROUNAGHI, GHOLAM; SADAT HOSSEINY, MALIHE; SADEGHIAN, HAMID (Asian Journal of Chemistry, 2010)
Competitive permeation of 7 metal ions from an aqueous source phase containing equimolar concentrations of cobalt(II), copper(II), chromium(III), silver(I), cadmium(II), zinc(II) and lead(II) metal cations at pH = 5 into an aqueous receiving phase at pH = 3 through an organic phase facilitated by a new synthesized lipophilic crown ether, 1,4-dioxa- 7,10-dithiacyclododecane-2,3-dione, as an ionophore was studied as bulk liquid membrane transport. The obtained results show that the ionophore is highly selective ionophore for silver ion and under the employed experimental conditions, it transport only this metal cation among the seven studied metal cations. The effects of various organic solvents on cation transport rates have been demonstrated. Among the organic solvents involving dichloromethane (DCM), 1,2-dichloroethane (1,2-DCE), chloroform (CHCl3) and nitrobenzene (NB) which were used as liquid membrane, the most transport rate was obtained for Ag(I) cation in dichloromethane. The sequence of transport rate for silver ion in organic solvents was: DCM > NB > CHCl3 > 1,2-DCE. A linear relationship was observed between the transport rate of silver ion and the composition of CHCl3- DCM, but a non-linear behaviour was found in the case of CHCl3-NB. The influence of the stearic, palmetic and oleic acids as surfactant in the membrane phase on the transport of metal cations was also investigated.